A new Tuskegee? Unethical human experimentation and Western neocolonialism in the mass circumcision of African men. Issue 4 (9th September 2020) - Fish, Max; Shahvisi, Arianne; Gwaambuka, Tatenda; Tangwa, Godfrey B.; Ncayiyana, Daniel; Earp, Brian D.
Abstract: Campaigns to circumcise millions of boys and men to reduce HIV transmission are being conducted throughout eastern and southern Africa, recommended by the World Health Organization and implemented by the United States government and Western NGOs. In the United States, proposals to mass‐circumcise African and African American men are longstanding, and have historically relied on racist beliefs and stereotypes. The present campaigns were started in haste, without adequate contextual research, and the manner in which they have been carried out implies troubling assumptions about culture, health, and sexuality in Africa, as well as a failure to properly consider the economic determinants of HIV prevalence. This critical appraisal examines the history and politics of these circumcision campaigns while highlighting the relevance of race and colonialism. It argues that the "circumcision solution" to African HIV epidemics has more to do with cultural imperialism than with sound health policy, and concludes that African communities need a means of robust representation within the regime.